The usage, constraints and preferences of green space at disadvantage neighborhood: a review of empirical evidence - Chenyang, Dai; Maruthaveeran, Sreetheran; Shahidan, Mohd Fairuz (Elsevier GmbH, 2022)
Neighborhood green space is closely related to the lives of every city dweller. However, some evidence showed that residents in disadvantaged neighborhoods do not fully use the green space due to quality, safety, and distance issues. Therefore, it is essential to understand how disadvantaged groups interact and use green space in these communities. However, there is still a lack of comprehensive evaluation. This research systematically sorts out the relevant literature and collects various attributes of the use, constraints, and preferences of the residents of disadvantaged neighborhoods on the green space through a systematic review method from the perspective of social ecology. Through a literature review of 4 databases (Science Direct, Scopus, web of science, and CNKI), 42 articles (N = 42) were finally included. This article concerns peer-reviewed papers published between 2008 and 2021. The research results showed that residents of disadvantaged communities' use of nearby green space are affected by personal, social, physical, and other attributes. Finally, a conceptual framework for the use, constraints, and preferences of disadvantaged neighborhood green space is proposed to help planners and designers design and improve community green space more effectively and ultimately achieve a harmonious living environment that meets various needs.